Genetic or Autoimmune: POLG-Related Epilepsy Initially Treated as an Autoimmune Encephalitis, a Case Report. (January 2021) - Shah, Suma; Berezoski, Abigail; Rahman, Shareena; Eckstein, Christopher; Luedke, Matthew
Hospital neurologists participate at the forefront of managing fulminant acute and subacute onset epilepsy, frequently attributed to autoimmune encephalitis (AE). As the recognition of antibody-mediated AE grows, there is a growing number of patients who are treated as antibody-negative AE. While antibody-negative autoimmune processes should be considered in the setting of acute and subacute onset of fulminant epilepsy, other causes must be considered before subjecting patients to long-term immunomodulatory treatments and other potential therapeutic toxicities. We present the case of a previously healthy young man who presented with new-onset refractory seizures treated with escalating doses of anti-epileptic drugs as well as immunosuppression for presumed autoimmune epilepsy. He developed valproic acid induced hepatotoxicity requiring liver transplantation and was later found to have a POLG mutation. We discuss the presentation of POLG mutations as well as the diagnosis of seronegative autoimmune encephalitis. We highlight the need for a broad differential when evaluating new onset refractory seizures in an otherwise healthy person.